Devising an automated method for experimental measurement of the rotor inertia moment in low-power asynchronous generators of renewable energy sources - Honcharuk, Inna; Hraniak, Valerii; Tokarchuk, Oleksii; Tokarchuk, Dina (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the electromechanical transient process in low-power asynchronous generators, suitable for operation in conjunction with renewable energy sources, when applying and removing the supply voltage, as well as the influence of the rotor moment of inertia of a low-power asynchronous generator on the duration of the specified transient process. The study addresses the task of reducing the complexity and duration of the pre-operational testing of the specified equipment. A new automated method for measuring the rotor moment of inertia has been proposed, which is based on the excitation of the generator under the motor mode of operation by the rated frequency voltage under the conditions of mechanical braking of the rotor. The specified measurement method is characterized by reasonable accuracy, high speed, and is suitable for use under both production and laboratory conditions. Within the framework of the study, a structural diagram of a technical means that implements the proposed method in practice has bene designed; a corresponding mathematical model of the electromechanical system “induction motor – measuring converter” was derived. A detailed metrological analysis revealed that the methodological error of the proposed method does not exceed 8%, which is acceptable for most applied tasks. A linear relationship between the parameters of the transient process and the characteristics of the electromechanical system was also established, which significantly simplifies the calibration of the device and increases the accuracy and repeatability of the measurement results. The research results confirm the high efficiency and practical feasibility of using the proposed approach in the field of technical control, maintenance and modernization of electric drive systems. The method could be adapted for a wide range of models of induction motors, as well as integrated into automated equipment condition monitoring systems